Os infiéis: uma análise da crítica na montagem de Romeu e Julieta do Grupo Galpão - MG - Campos, Naiara Dias da Silva (2016)
This study consists in the analysis of the play Romeo and Juliet performed by Grupo Galpão through the critic’s point of view. The Grupo Galpão legitimated itself in the Brazilian drama scenario in the early nineties. Some of the choices of the troupe made this dramaturgical production unusual, which brought the critic’s attention to analyze the play, considering that it has brought a classic to streets, filling it with popular language and characteristically Brazilians elements. This research will discuss the drama performance based on the critic’s point of view, an uncommon practice at the Academia. We, therefore, propose to look the critics, deliberating its potencies and scope, pondering the strength the play has acquired with time, becoming later a reference of the Shakespearean play Romeo and Juliet.